The effects of nonlocal impact ionization on the speed of avalanche photodiodes. - Hambleton, P.J.
The nonlocal enhancement in the velocities of charge carriers to ionization is shown to outweigh the opposing effects of dead space, increasing the avalanche speed of short avalanche photodiodes (APDs) over the predictions of a conventional local model which ignores both of these effects. The trends in the measured gain-bandwidth product of two short InAlAs APDs reported in the literature support this result. Relatively large speed benefits are predicted to result from further small reductions in the lengths of short multiplication regions.
Keywords: InAlAs; InAlAs APDs; Monte Carlo modeling; Avalanche speed; Charge carrier velocity enhancement; Dead space; Frequency response; Gain-bandwidth product; Nonlocal enhancement; Nonlocal impact ionization; Short avalanche photodiodes; Short multiplication regions